Ultraviolet-aging-resistant meta-aramid paper as well as preparation method and application thereof

By adding nano-metal oxides during the preparation of meta-aramid paper and utilizing descaling, pulping, and hot pressing processes, the problem of insufficient UV aging resistance in existing meta-aramid paper has been solved, thus realizing the preparation of high-performance aramid paper.

CN119265994AActive Publication Date: 2025-01-07ELECTRIC POWER RES INST OF GUANGDONG POWER GRID CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411626761.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-07
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Existing preparation methods are insufficient for producing high-performance meta-aramid paper, especially in terms of its low resistance to ultraviolet aging.

Method used

Nanoscale metal oxides with UV resistance, such as nanoscale titanium dioxide and nanoscale zinc oxide, are added during the preparation process. Meta-aramid paper with UV resistance is prepared through pulping, sheet forming and hot pressing processes.

Benefits of technology

It improves the tensile strength and stability of aramid paper, reduces amide bond breakage caused by ultraviolet light energy, expands the wavelength range for UV aging resistance, and enhances the reliability and stability of the paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265994A_ABST
    Figure CN119265994A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aramid paper, and particularly relates to anti-ultraviolet aging meta-aramid paper as well as a preparation method and application thereof. According to the preparation method of the anti-ultraviolet aging meta-position aramid paper, a fluffer is firstly used for fluffing and pulping, then a sheet making machine is used for forming pulp, and then a hot press is used for hot pressing. The nano metal oxide with anti-ultraviolet performance added in the defibering and pulping process can be uniformly dispersed in the meta-aramid paper, so that the anti-ultraviolet performance is fully exerted, and the meta-aramid paper is endowed with excellent anti-ultraviolet aging performance; by adjusting the nano metal oxide with the anti-ultraviolet performance and carrying out ultrasonic treatment on the nano metal oxide with the anti-ultraviolet performance in advance, the excellent anti-ultraviolet aging performance of the meta-aramid paper can be further improved, and the technical problem that the high-performance meta-aramid paper is difficult to prepare through an existing preparation method is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of aramid paper, and in particular relates to a meta-aramid paper resistant to ultraviolet aging, a preparation method and an application thereof. Background Art

[0002] Aramid paper (polyaramid fiber paper) is a new functional material with high strength, low deformation, high temperature resistance, chemical corrosion resistance, flame retardancy and excellent electrical insulation properties. It is often used in high-speed rail transportation, aerospace, electrical insulation and other fields.

[0003] Depending on the materials used, aramid paper is divided into meta-aramid paper and para-aramid paper. Meta-aramid paper is prepared by using a deflaking machine, a sheet making machine, a hot press and other equipment to process meta-aramid precipitated fibers and meta-aramid chopped fibers through steps such as papermaking, pressing, drying and hot pressing. The aramid fiber used in meta-aramid paper is a light-sensitive material. When exposed to fluorescent lamps or ultraviolet lamps for a long time, when the energy provided by ultraviolet light is completely greater than the energy required for the break of the amide bond, the breakage of the amide bond will change the molecular structure of the aramid and the performance of the meta-aramid paper will decrease. By reducing the breakage of the amide bonds of aramid fibers caused by light and improving the ability of meta-aramid paper to resist ultraviolet aging, the reliability and stability of aramid paper can be improved, which is expected to meet the requirements of high-quality development in high-speed rail transit, aerospace, electrical insulation and other fields.

[0004] However, the current research on meta-aramid paper is not in-depth enough, and the performance of meta-aramid paper prepared using meta-aramid fibrils and meta-aramid chopped fibers as raw materials is relatively low. Summary of the invention

[0005] In view of this, the present application provides an anti-ultraviolet aging meta-aramid paper and a preparation method and application thereof, which are used to solve the technical problem that the existing preparation methods are difficult to prepare high-performance meta-aramid paper.

[0006] The first aspect of the present application provides a method for preparing ultraviolet aging resistant meta-aramid paper, the preparation method comprising the steps of:

[0007] Step S1, adding nano-metal oxides with anti-ultraviolet properties and meta-aramid fibrids into a deflaking machine for deflaking and pulping to obtain meta-aramid fibrid slurry doped with nano-metal oxides;

[0008] Step S2, adding the meta-aramid short fibers treated with a surfactant and the meta-aramid fibrillation slurry doped with nano-metal oxides into a sheet making machine, and sequentially performing paper making, pressing, and drying to obtain formed meta-aramid paper;

[0009] Step S3: hot-pressing the formed meta-aramid paper using a hot press to obtain ultraviolet aging-resistant meta-aramid paper.

[0010] Preferably, in step S1, the step of adding the nano metal oxide with anti-ultraviolet properties and meta-aramid fibrils into a deflaker for deflaking and pulping is specifically as follows: adding at least one of nano titanium dioxide particles, nano zinc oxide particles, and nano silicon dioxide particles and meta-aramid fibrils into a deflaker for deflaking and pulping.

[0011] Preferably, in step S1, the step of adding the nano metal oxide with anti-ultraviolet properties and meta-aramid fibrils into a deflaker for deflaking and beating is specifically as follows: adding nano titanium dioxide particles, nano zinc oxide particles and meta-aramid fibrils in a mass ratio of 1:0.5-2 into a deflaker for deflaking and beating.

[0012] Preferably, in step S1, the step of adding the anti-ultraviolet nano-metal oxide and meta-aramid fibrils into a deflaker for deflaking and beating is specifically as follows: adding the anti-ultraviolet nano-metal oxide and meta-aramid fibrils with a particle size of 30-100 nm into a deflaker for deflaking and beating.

[0013] Preferably, in step S1, the step of adding the anti-ultraviolet nano-metal oxide and meta-aramid fibrils into a deflaker for deflaking and beating is specifically as follows: ultrasonically dispersing the anti-ultraviolet nano-metal oxide and water and adding the meta-aramid fibrils into a deflaker for deflaking and beating.

[0014] Preferably, in step S1, the step of adding the nano-metal oxide with anti-ultraviolet properties and meta-aramid fibrils into a deflaker for deflaking and beating to obtain meta-aramid fibrils slurry doped with nano-metal oxides is specifically as follows: adding the nano-metal oxide with anti-ultraviolet properties and meta-aramid fibrils into a deflaker for deflaking and beating to obtain meta-aramid fibrils slurry doped with nano-metal oxides having a beating degree of 30°SR~80°SR.

[0015] Preferably, in step S1, the step of adding the nano-metal oxide with anti-ultraviolet properties and meta-aramid fibrils into a deflaker for deflaking and beating to obtain meta-aramid fibrils slurry doped with nano-metal oxides is specifically as follows: adding the nano-metal oxide with anti-ultraviolet properties and meta-aramid fibrils into a deflaker for deflaking and beating to obtain meta-aramid fibrils slurry doped with nano-metal oxides having a deflaking concentration of 0.1% to 0.3%.

[0016] In step S2, the step of adding the meta-aramid chopped fibers treated with a surfactant and the meta-aramid fibrillation slurry doped with nano-metal oxides into a sheet making machine is specifically as follows: adding the meta-aramid chopped fibers of 1 mm to 10 mm treated with a surfactant and the meta-aramid fibrillation slurry doped with nano-metal oxides into a sheet making machine.

[0017] Preferably, in step S3, the temperature of the hot pressing is 250-300° C., the pressure is 2 MPa-5 MPa, and the roller speed is 5 m / min-15 m / min.

[0018] The second aspect of the present application provides a meta-aramid paper resistant to ultraviolet aging, which is prepared by the preparation method of the meta-aramid paper resistant to ultraviolet aging described in the first aspect.

[0019] The third aspect of the present application provides the use of the anti-ultraviolet aging meta-aramid paper described in the second aspect in the field of high-speed rail transportation, aerospace or electrical insulation.

[0020] In summary, the present application provides a meta-aramid paper with UV resistance, a preparation method and an application. The preparation method of the meta-aramid paper with UV resistance provided by the present application comprises firstly adding nano-metal oxides with UV resistance and meta-aramid fibrils into a deflaking machine for deflaking and pulping to obtain meta-aramid fibrils slurry doped with nano-metal oxides; then adding meta-aramid chopped fibers treated with a surfactant and meta-aramid fibrils slurry doped with nano-metal oxides into a sheet making machine, and sequentially performing papermaking, forming, pressing and drying to obtain formed meta-aramid paper; then hot pressing the formed meta-aramid paper using a hot press to obtain meta-aramid paper with UV resistance; adding in the preparation method The nano-metal oxide with anti-ultraviolet properties can reduce the breakage of amide bonds caused by ultraviolet light energy, improve the stability of the aramid molecular structure, and is beneficial to the long-term maintenance of the tensile strength and other properties of meta-aramid paper. The added nano-metal oxide with anti-ultraviolet properties is added during the deflaking and beating process. The high-intensity impact and shear force applied by the action between the high-speed rotating rotor and the stator of the deflaking machine during the deflaking and beating process can improve the dispersibility of the nano-metal oxide, which is beneficial to the full play of the anti-ultraviolet properties of the nano-metal oxide. Meta-aramid paper with excellent resistance to ultraviolet aging can be prepared, thereby solving the technical problem that the existing preparation method is difficult to prepare high-performance meta-aramid paper. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0022] Figure 1 A schematic flow chart of a method for preparing ultraviolet aging resistant meta-aramid paper provided in the present application. DETAILED DESCRIPTION

[0023] The present application provides an ultraviolet aging-resistant meta-aramid paper and a preparation method and application thereof, which are used to solve the technical problem that the existing preparation methods are difficult to prepare high-performance meta-aramid paper.

[0024] The technical solution of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0025] In view of the defect of low performance of the currently prepared meta-aramid paper, the present application provides a method for preparing meta-aramid paper with resistance to ultraviolet aging, the preparation method comprising: firstly adding nano-metal oxides with anti-ultraviolet performance and meta-aramid fibrils into a deflaking machine for deflaking and pulping to obtain meta-aramid fibrils slurry doped with nano-metal oxides; then adding meta-aramid chopped fibers treated with a surfactant and meta-aramid fibrils slurry doped with nano-metal oxides into a sheet making machine, and sequentially performing papermaking, pressing and drying to obtain formed meta-aramid paper; and then hot pressing the formed meta-aramid paper using a hot press to obtain meta-aramid paper with resistance to ultraviolet aging.

[0026] In the preparation method of meta-aramid paper with resistance to ultraviolet aging provided in the present application, pulp is first obtained by using a deflaking machine to deflake and beat pulp, and then the pulp is prepared into meta-aramid paper by using a sheet making machine, and then the meta-aramid paper is hot-pressed by using a hot press; the nano-metal oxide added in the preparation process refers to metal oxide particles with a particle size of less than 100 nanometers, which have unique physical and chemical properties. Some nano-metal oxides, such as nano-titanium dioxide particles, nano-zinc oxide particles and nano-silicon dioxide particles, have anti-ultraviolet ability and are nano-metal oxides with anti-ultraviolet properties; the nano-metal oxide particles with anti-ultraviolet properties are doped into the meta-aramid paper, which can reduce the amide bond breakage caused by ultraviolet light energy, and the aramid molecular structure is difficult to change, and the tensile strength and other properties of the meta-aramid paper are maintained for a long time. The meta-aramid paper is not easy to age due to ultraviolet radiation, thereby improving the anti-ultraviolet aging of the meta-aramid paper. The nano-metal oxide with anti-ultraviolet property is added in the process of deflaking and beating. In the process of deflaking and beating, the high-speed rotating rotor and stator of the deflaking machine exert high-intensity impact and shear force on the nano-metal oxide and meta-aramid fibrils, which can not only change the morphology of meta-aramid fibrils, but also change the morphology and surface energy of the nano-metal oxide, and promote the dispersibility of the nano-metal oxide. The nano-metal oxide is added in the process of deflaking and beating instead of the slurry forming process, which increases the contact and adhesion time between the nano-metal oxide and the fibrils, reduces the defects of easy flocculation and difficulty in dispersing the slurry and the nano-metal oxide, and improves the dispersibility of the nano-metal oxide by adjusting the preparation process, which is conducive to giving full play to the anti-ultraviolet property of the nano-metal oxide. Thus, the defect of low performance of the meta-aramid paper currently prepared is overcome.

[0027] Preferably, in the preparation method of the anti-ultraviolet aging meta-aramid paper provided in the present application, the added nano metal oxide with anti-ultraviolet performance is obtained by compounding nano titanium dioxide particles and nano zinc oxide particles. Nano titanium dioxide particles are expensive, while nano zinc oxide is relatively cheap. The compounding of the two can reduce the cost of nano metal oxide; and the nano titanium dioxide particles and nano zinc oxide have different resistance to ultraviolet wavelengths. Within the ultraviolet wavelength range of 10 to 400 nm, the nano titanium dioxide particles have a better anti-ultraviolet aging effect for wavelengths of 290 to 350 nm, while the nano zinc oxide has a better anti-ultraviolet aging effect for wavelengths above 350 nm. By compounding the nano titanium dioxide particles and nano zinc oxide particles, the wavelength range of the nano metal oxide's resistance to ultraviolet aging can be made wider.

[0028] Preferably, in the method for preparing the ultraviolet aging resistant meta-aramid paper provided in the present application, the particle size of the nano metal oxide with ultraviolet resistance is selected from 30 to 100 nm.

[0029] Preferably, in the preparation method of the anti-ultraviolet aging meta-aramid paper provided in the present application, in order to further promote the dispersibility of the nano-metal oxide with anti-ultraviolet properties, the nano-metal oxide with anti-ultraviolet properties and water can be ultrasonically dispersed in advance before adding them in the pulping process.

[0030] The following is a detailed description of the nano metal oxide with anti-ultraviolet properties provided by the present application in combination with the embodiments and experimental examples.

[0031] Example 1

[0032] Example 1 of the present application provides a method for preparing ultraviolet aging-resistant meta-aramid paper, the preparation method comprising the steps of: using a deflaker to perform deflaking and pulping, using a sheet making machine to shape the pulp, and using a hot press to perform hot pressing.

[0033] Among them, the step of using a deflaking machine for deflaking and beating includes: ultrasonically treating 1kg of nano zinc oxide and 10kg of water to make a suspension, and adding 6kg of meta-aramid fiber and 3483kg into the deflaking machine for deflaking and beating to obtain a meta-aramid fiber slurry doped with nano metal oxide with a deflaking concentration of 0.23% and a beating degree of 70°SR.

[0034] The steps of using a sheet making machine to shape the slurry include: using 0.01 mol / L sodium dodecylbenzene sulfonate solution to treat 3 kg of meta-chopped fibers (7 mm) for 30 minutes to obtain meta-aramid chopped fibers treated with a surfactant, adding the meta-aramid chopped fibers treated with a surfactant and the meta-aramid precipitated fiber slurry doped with nano-metal oxides into a sheet making machine, and sequentially performing papermaking shaping, pressing, and drying to obtain shaped meta-aramid paper.

[0035] The step of using a hot press to perform hot pressing includes: using the hot press to perform hot pressing on the formed meta-aramid paper at a temperature of 280° C., a pressure of 4 Mpa, and a roller speed of 10 m / min to obtain the meta-aramid paper resistant to ultraviolet aging.

[0036] Example 2

[0037] Example 2 of the present application provides a method for preparing ultraviolet aging-resistant meta-aramid paper. The difference between the preparation method and Example 1 is that the nano metal oxide with ultraviolet resistance is adjusted. The preparation method includes the steps of: using a deflaker to deflake and pulp, using a sheet making machine to shape the pulp, and using a hot press to perform hot pressing.

[0038] Among them, the step of using a deflaker to carry out deflaking and beating includes: ultrasonically treating 0.5kg of nano zinc oxide, 0.5kg of nano titanium dioxide and 10kg of water to make a suspension, and adding 6kg of meta-aramid fiber and 3483kg into the deflaker for deflaking and beating to obtain a meta-aramid fiber slurry doped with nano metal oxides with a deflaking concentration of 0.23% and a beating degree of 70°SR.

[0039] The steps of using a sheet making machine to shape the slurry include: using 0.01 mol / L sodium dodecylbenzene sulfonate solution to treat 3 kg of meta-chopped fibers (7 mm) for 30 minutes to obtain meta-aramid chopped fibers treated with a surfactant, adding the meta-aramid chopped fibers treated with a surfactant and the meta-aramid precipitated fiber slurry doped with nano-metal oxides into a sheet making machine, and sequentially performing papermaking shaping, pressing, and drying to obtain shaped meta-aramid paper.

[0040] The step of using a hot press to perform hot pressing includes: using the hot press to perform hot pressing on the formed meta-aramid paper at a temperature of 280° C., a pressure of 4 Mpa, and a roller speed of 10 m / min to obtain the meta-aramid paper resistant to ultraviolet aging.

[0041] Example 3

[0042] Example 3 of the present application provides a method for preparing ultraviolet aging-resistant meta-aramid paper. The difference between the preparation method and Example 2 lies in that the process of adding nano-metal oxides with anti-ultraviolet properties is adjusted. The preparation method comprises the steps of: using a deflaker to perform deflaking and pulping, using a sheet making machine to form the pulp, and using a hot press to perform hot pressing.

[0043] Among them, the step of using a deflaker for deflaking and pulping includes: adding 0.5kg of nano zinc oxide, 0.5kg of nano titanium dioxide, 6kg of meta-aramid fiber and 2993kg of nano-aramid fiber to the deflaker for deflaking and pulping to obtain a meta-aramid fiber slurry doped with nano-metal oxide with a deflaking concentration of 0.23% and a beating degree of 70°SR.

[0044] The steps of using a sheet making machine to shape the slurry include: using 0.01 mol / L sodium dodecylbenzene sulfonate solution to treat 3 kg of meta-chopped fibers (7 mm) for 30 minutes to obtain meta-aramid chopped fibers treated with a surfactant, adding the meta-aramid chopped fibers treated with a surfactant and the meta-aramid precipitated fiber slurry doped with nano-metal oxides into a sheet making machine, and sequentially performing papermaking shaping, pressing, and drying to obtain shaped meta-aramid paper.

[0045] The step of using a hot press to perform hot pressing includes: using the hot press to perform hot pressing on the formed meta-aramid paper at a temperature of 280° C., a pressure of 4 Mpa, and a roller speed of 10 m / min to obtain the meta-aramid paper resistant to ultraviolet aging.

[0046] Example 4

[0047] Example 4 of the present application provides a method for preparing ultraviolet aging-resistant meta-aramid paper. The difference between the preparation method and Example 2 is that the meta-chopped fibers are adjusted. The preparation method includes the steps of: using a deflaker to perform deflaking and pulping, using a sheet making machine to form the pulp, and using a hot press to perform hot pressing.

[0048] Among them, the step of using a deflaker for deflaking and pulping includes: adding 0.5kg of nano zinc oxide, 0.5kg of nano titanium dioxide, 6kg of meta-aramid fiber and 2993kg of nano-aramid fiber to the deflaker for deflaking and pulping to obtain a meta-aramid fiber slurry doped with nano-metal oxide with a deflaking concentration of 0.23% and a beating degree of 70°SR.

[0049] The steps of using a sheet making machine to shape the slurry include: using 0.01 mol / L sodium dodecylbenzene sulfonate solution to treat 3 kg of meta-chopped fibers (5 mm) for 30 minutes to obtain meta-aramid chopped fibers treated with a surfactant, adding the meta-aramid chopped fibers treated with a surfactant and the meta-aramid precipitated fiber slurry doped with nano-metal oxides into a sheet making machine, and sequentially performing papermaking shaping, pressing, and drying to obtain shaped meta-aramid paper.

[0050] The step of using a hot press to perform hot pressing includes: using the hot press to perform hot pressing on the formed meta-aramid paper at a temperature of 280° C., a pressure of 4 Mpa, and a roller speed of 10 m / min to obtain the meta-aramid paper resistant to ultraviolet aging.

[0051] Example 5

[0052] Example 5 of the present application provides a method for preparing ultraviolet aging-resistant meta-aramid paper. The difference between the preparation method and Example 4 is that the amount of raw materials is adjusted. The preparation method includes the steps of: using a deflaker to deflake and beat the pulp, using a sheet making machine to shape the pulp, and using a hot press to perform hot pressing.

[0053] Among them, the step of using a deflaker for deflaking and pulping includes: adding 1kg of nano zinc oxide, 1kg of nano titanium dioxide, 5kg of meta-aramid fiber and 2993kg into the deflaker for deflaking and pulping to obtain a meta-aramid fiber slurry doped with nano metal oxide with a deflaking concentration of 0.23% and a beating degree of 70°SR.

[0054] The steps of using a sheet making machine to shape the slurry include: using 0.01 mol / L sodium dodecylbenzene sulfonate solution to treat 3 kg of meta-chopped fibers (5 mm) for 30 minutes to obtain meta-aramid chopped fibers treated with a surfactant, adding the meta-aramid chopped fibers treated with a surfactant and the meta-aramid precipitated fiber slurry doped with nano-metal oxides into a sheet making machine, and sequentially performing papermaking shaping, pressing, and drying to obtain shaped meta-aramid paper.

[0055] The step of using a hot press to perform hot pressing includes: using the hot press to perform hot pressing on the formed meta-aramid paper at a temperature of 280° C., a pressure of 4 Mpa, and a roller speed of 10 m / min to obtain the meta-aramid paper resistant to ultraviolet aging.

[0056] Example 6

[0057] Example 6 of the present application provides a method for preparing ultraviolet aging-resistant meta-aramid paper. The difference between the preparation method and Example 4 is that the amount of raw materials is adjusted. The preparation method includes the steps of: using a deflaker to deflake and beat the pulp, using a sheet making machine to shape the pulp, and using a hot press to perform hot pressing.

[0058] Among them, the step of using a deflaker to carry out deflaking and pulping includes: adding 0.5kg of nano zinc oxide, 0.5kg of nano titanium dioxide, 5.5kg of meta-aramid fiber and 2993.5kg into the deflaker for deflaking and pulping to obtain a meta-aramid fiber slurry doped with nano metal oxide with a deflaking concentration of 0.22% and a beating degree of 70°SR.

[0059] The steps of using a sheet making machine to shape the slurry include: using 0.01 mol / L sodium dodecylbenzene sulfonate solution to treat 3.5 kg of meta-chopped fibers (5 mm) for 30 minutes to obtain meta-aramid chopped fibers treated with a surfactant, adding the meta-aramid chopped fibers treated with a surfactant and the meta-aramid precipitated fiber slurry doped with nano-metal oxides into a sheet making machine, and sequentially performing papermaking shaping, pressing, and drying to obtain shaped meta-aramid paper.

[0060] The step of using a hot press to perform hot pressing includes: using the hot press to perform hot pressing on the formed meta-aramid paper at a temperature of 280° C., a pressure of 4 Mpa, and a roller speed of 10 m / min to obtain the meta-aramid paper resistant to ultraviolet aging.

[0061] Example 7

[0062] Example 7 of the present application provides a method for preparing meta-aramid paper. As a comparative example, the preparation method includes the steps of: using a deflaker to perform deflaking and pulping, using a sheet making machine to shape the pulp, and using a hot press to perform hot pressing.

[0063] Among them, the step of using a deflaker to perform deflaking and beating includes: adding 6kg of meta-aramid fibrils and 2994kg of meta-aramid fibrils into the deflaker for deflaking and beating to obtain a meta-aramid fibril slurry with a deflaking concentration of 0.2% and a beating degree of 70°SR.

[0064] The steps of using a sheet making machine to shape the slurry include: using 0.01 mol / L sodium dodecylbenzene sulfonate solution to treat 4 kg of meta-chopped fibers (7 mm) for 30 minutes to obtain meta-aramid chopped fibers treated with a surfactant, adding the meta-aramid chopped fibers treated with a surfactant and the meta-aramid precipitated fiber slurry into a sheet making machine, and sequentially performing papermaking shaping, pressing, and drying to obtain shaped meta-aramid paper.

[0065] The step of using a hot press to perform hot pressing includes: using the hot press to perform hot pressing on the formed meta-aramid paper at a temperature of 280° C., a pressure of 4 Mpa, and a roller speed of 10 m / min to obtain the meta-aramid paper.

[0066] Experimental Example 1

[0067] Experimental Example 1 of the present application performs performance tests on the ultraviolet aging resistant meta-aramid paper and meta-aramid paper provided in Examples 1-7.

[0068] The performance test process is as follows: first, the ultraviolet aging resistant meta-aramid paper and meta-aramid paper provided in Examples 1-7 are subjected to a tensile strength test according to the national standard GB / T12914-2008, and then the ultraviolet aging resistant meta-aramid paper and meta-aramid paper provided in Examples 1-7 are subjected to ultraviolet aging for 80 hours and 160 hours according to the national standard GB / T 16422.3-2022, and their tensile strengths are tested respectively according to the national standard GB / T12914-2008, to obtain the tensile strength performance test results shown in Table 1.

[0069] Table 1: Tensile strength test results

[0070]

[0071] It can be seen from the test results shown in Table 1 that in Example 7 as a comparative example, nano-metal oxides with anti-ultraviolet properties such as nano-titanium dioxide and nano-zinc oxide were not added during the preparation of the meta-aramid paper, which makes it easy for the amide bonds of the aramid molecules in the meta-aramid paper to break when exposed to ultraviolet light, so that the tensile strength of the meta-aramid paper decreases rapidly, decaying by 12% after 80 hours of ultraviolet irradiation and by 22% after 160 hours, with only 78% of the original tensile strength.

[0072] In the process of preparing meta-aramid paper in Examples 1-6, nano-metal oxides with anti-ultraviolet properties such as nano-titanium dioxide and nano-zinc oxide are added, which makes it difficult for the amide bonds of the aramid molecules in the meta-aramid paper to break when exposed to ultraviolet light, and the tensile strength of the meta-aramid paper is not easy to decrease, thus the meta-aramid paper is resistant to ultraviolet aging.

[0073] Further comparison of the meta-aramid papers prepared in Examples 1-6 shows that the only nano-metal oxide with anti-ultraviolet properties added to the anti-ultraviolet meta-aramid paper provided in Example 1 is nano-zinc oxide. Although the cost of nano-zinc oxide is lower, the rate of decrease in the tensile strength of the meta-aramid paper is greater than that of the anti-ultraviolet meta-aramid paper provided in Example 2. This is because the anti-ultraviolet meta-aramid paper provided in Example 2 uses a compound of nano-zinc oxide and nano-titanium dioxide, which makes the anti-ultraviolet wavelength range of the anti-ultraviolet meta-aramid paper wider, so that the rate of decrease in tensile strength is slower.

[0074] Further comparison of the meta-aramid papers prepared in Examples 1-6 shows that, although the anti-ultraviolet aging meta-aramid paper provided in Example 3 is added with compounded nano-zinc oxide and nano-titanium dioxide, the compounded nano-zinc oxide and nano-titanium dioxide are not pre-ultrasonic dispersed, which makes the rate of decrease in the tensile strength of the meta-aramid paper greater than that of the anti-ultraviolet aging meta-aramid paper provided in Example 2.

[0075] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing ultraviolet aging resistant meta-aramid paper, characterized in that: Includes steps: Step S1, adding nano-metal oxides with anti-ultraviolet properties and meta-aramid fibrids into a deflaking machine for deflaking and pulping to obtain meta-aramid fibrid slurry doped with nano-metal oxides; Step S2, adding the meta-aramid short fibers treated with a surfactant and the meta-aramid fibrillation slurry doped with nano-metal oxides into a sheet making machine, and sequentially performing paper making, pressing, and drying to obtain formed meta-aramid paper; Step S3: hot-pressing the formed meta-aramid paper using a hot press to obtain ultraviolet aging-resistant meta-aramid paper.

2. The method for preparing a meta-aramid paper resistant to ultraviolet aging according to claim 1, characterized in that: Step S1 specifically includes: adding at least one of nano titanium dioxide particles, nano zinc oxide particles, and nano silicon dioxide particles and meta-aramid fibrids into a deflaker for deflaking and pulping to obtain meta-aramid fibrid slurry doped with nano metal oxides.

3. The method for preparing a meta-aramid paper resistant to ultraviolet aging according to claim 1, characterized in that: Step S1 specifically includes: adding nano titanium dioxide particles, nano zinc oxide particles and meta-aramid fibrids in a mass ratio of 1:0.5-2 into a deflaker for deflaking and pulping to obtain meta-aramid fibrid slurry doped with nano metal oxides.

4. The method for preparing a meta-aramid paper resistant to ultraviolet aging according to claim 1, characterized in that: Step S1 specifically includes: adding nano-metal oxides with anti-ultraviolet properties and a particle size of 30-100 nm and meta-aramid fibrids into a deflaker for deflaking and pulping to obtain meta-aramid fibrid slurry doped with nano-metal oxides.

5. The method for preparing a meta-aramid paper resistant to ultraviolet aging according to claim 1, characterized in that: Step S1 specifically includes: subjecting the nano-metal oxide with anti-ultraviolet property and water to ultrasonic dispersion treatment, and adding the meta-aramid fibrid to a deflaking machine for deflaking and pulping to obtain meta-aramid fibrid slurry doped with nano-metal oxide.

6. The method for preparing a meta-aramid paper resistant to ultraviolet aging according to claim 1, characterized in that: Step S1 specifically includes: adding nano-metal oxides with anti-ultraviolet properties and meta-aramid fibrils into a deflaking machine for deflaking and beating to obtain meta-aramid fibrils slurry doped with nano-metal oxides having a beating degree of 30°SR~80°SR and a deflaking concentration of 0.1%~0.3%.

7. The method for preparing a meta-aramid paper resistant to ultraviolet aging according to claim 1, characterized in that: Step S2 specifically includes: adding 1mm~10mm meta-aramid short fibers treated with a surfactant and meta-aramid fibrillation slurry doped with nano-metal oxides into a sheet making machine, and sequentially performing papermaking, pressing, and drying to obtain formed meta-aramid paper.

8. The method for preparing a meta-aramid paper resistant to ultraviolet aging according to claim 1, characterized in that: Step S3 specifically includes: hot pressing the formed meta-aramid paper using a hot press at a temperature of 250-300° C., a pressure of 2Mpa-5Mpa, and a roller speed of 5m / min-15m / min to obtain ultraviolet aging-resistant meta-aramid paper.

9. A meta-aramid paper resistant to ultraviolet aging, characterized in that: The paper is prepared by the method for preparing the ultraviolet aging resistant meta-aramid paper according to any one of claims 1 to 8.

10. Use of the ultraviolet aging resistant meta-aramid paper according to claim 9 in the field of high-speed rail transportation, aerospace or electrical insulation.

Citation Information

Patent Citations

  • Nano-TiO2 doped anti-ultraviolet para-aramid nanopaper and preparation method thereof

    CN110387770A

  • Aramid fiber insulation paper winding equipment

    CN212375631U

  • Method for producing meta-aramid fiber paper-based material

    US20170073896A1